Biophysical Drivers of Zooplankton Variability on the Scotian Shelf Observed Using Profiling Electric Gliders - Ruckdeschel, Gennavieve S.; Davies, Kimberley T. A.; Ross, Tetjana (Frontiers in Marine Science, 2020)
Variation in water mass transport is a key driver of variability in zooplankton ecology. Data distribution (e.g., sparseness) is often an important factor limiting robust delineation of zooplankton-water mass associations. Mobile autonomous profiling gliders can help address the sparseness issue because gliders can sample across water mass domains spanning tens to hundreds of kilometers at high frequency during a single deployment. The goal of our study was to research the use of gliders as a tool to increase the spatiotemporal scale and robustness of zooplankton-water mass datasets. An autonomous ocean glider was deployed in Roseway Basin, Scotian Shelf, Canada for 2 months along a set of transects that crossed two water masses, a cold-fresh coastal water mass, and a warm-salty continental slope water mass. Zooplankton biomass was measured with a single frequency Imagenex 300 kHz hydroacoustic echosounder mounted to the underside of the glider at an angle of 26°, such that it was directed vertically downward on the glider downcast. During the deployment, an unusual basin flushing event occurred, where the slope water mass that is typically present in the deep water of Scotian Shelf basins was almost completely replaced by coastal water at all depths. This unique event offered an opportunity to study how extreme changes in water mass affected zooplankton distribution. The impact of basin flushing on both diel- and non diel-vertically migrating zooplankton communities within the basin was investigated using General Linear Models. The analysis demonstrated some key relationships exist among zooplankton acoustic scattering layers, water mass properties, and basin bathymetry. Zooplankton biomass was higher in the slope water mass, and declined substantially during the basin flushing event, suggesting that coastal water is not zooplankton habitat for either community. Spatial gradients in the extent of flushing provided local refuge for zooplankton within one margin of the Basin. These patterns would be challenging to measure using conventional shipboard surveys. Our study provides guidance on the use of gliders to supplement shipboard research on biophysical coupling in the plankton, which is of value as the use of gliders for this purpose is proliferating.